Sustainability Bisnis: Analisis Market Timing dan Stock Selection Reksa Dana Saham Indonesia - Dialysa, Fia; Dialysa, Fia; Dialysa, Fia (Universitas Islam Bandung, 2020)
The principle of business sustainability is sustainable development covering 3 (three) scopes, namely economic, social and environmental. Socially Responsible Investment (SRI) or ethical investment is one of the factors driving the implementation of sustainability principles by a company. This is closely related to the awareness of investors to invest with attention to social responsibility.This study aims to determine the ability of market timing and stock selection on Mutual Funds in Indonesia and the performance of each Mutual Fund share using the Sharpe method, Treynor method, and Jensen method. The data used are Net Asset Value (NAV), Bank Indonesia interest rates and the Composite Stock Price Index (CSPI). The sample used, 28 Mutual Funds products registered and active in the Financial Services Authority (OJK) during the period January 2014 to June 2017. The method used by using multiple linear regression methods.The results showed, the 28 stock Mutual Fund products studied, there were no stock Mutual Fund products had the ability in terms of market timing and there was only Sucorinvest Equity Fund. In addition, the performance of Mutual Fund shares in Indonesia has an overvalued stock value.Â Keywords: Sustainability, Stock Mutual Funds.